The effects of Urtica dioica L. ethanolic extract against urinary calculi in rats - DOĞAN, AHMET; ŞEN, ALİ; ERTAŞ, BÜŞRA; ŞENER, GÖKSEL; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE (MARMARA UNIV, 2020)
Nephrolithiasis is common urological problem and stone formation has multiple underlying pathogenetic factors. We investigated the possible preventive and therapeutic effect of Urtica dioica ethanol extract (UD) on ethylene glycol-induced nephrolithiasis model in rats. Sprague-Daw ley rats were divided into lour groups (n = 10). The control group was given normal drinking water for 8 weeks and was administered vehicle by gastric gavage. Stone formation was induced by adding 0.75% ethylene glycol (EG) to their drinking water. UD (700 mg/kg) was given orally lor 8 weeks to the preventive group and I or last 4 weeks to the treatment respectively. At the end of the experiment, urine, blood samples and kidney tissues were obtained. In 24-hour urine samples, calcium and citrate levels were decreased and oxalate levels were increased in EG whereas LID treatment groups reversed these parameters back to control levels. In addition, serum levels of creatinine and urea were increased in EG while LID significantly reduced these parameters. Malondialdehyde, 8-hydroxydeoxyguanosine and tumor necrosis alpha levels, and caspase- 3 and N-acetyl-beta-glucosaminidase activities were elevated in EG group and showed a decrease in LID treated groups. Glutathione level was decreased in EG group, whereas it was increased in UD preventive group. Histological examination showed an improvement in UD treated groups. Our results suggest that UD is effective both in prevention and treatment for kidney stones. The mechanism underlying this effect may be the antioxidant effect of UD and the effect on the concentration of stone-forming components in the urine.
Keywords: Urtica dioica; kidney stone; calcium oxalate; urolithiasis; antioxidant; GLYCOL-INDUCED UROLITHIASIS; ANTIOXIDANT; KIDNEY; NEPHROLITHIASIS; NEPHROTOXICITY; INFLAMMATION; INJURY